Community Radio Movement in India – Few Aspects Requiring Attention - Bora, Abhijit; Lakhendra, Bala (Richtmann Publishing, 2012)
The Community Radio movement in India was ushered in with high hopes and expectations in the 90s’ decade of thelast century. It was foreseen as a convenient and comprehensive instrument of development of the masses at grassroots level.However, over the years several factors and developments have undermined the original primary goals of the medium anddiverted it towards some not so important goals with passage of time, thereby depriving the organizations and citizensconcerned about deriving developmental benefits out of the medium. The author makes an effort at trying to analyze why this ishappening while at the same time discussing a brief development of the medium in the world of mass communication, speciallyin the Indian subcontinent. It is also sought to be seen if the Government of the country is somewhat wary of fully opening up thismedia for preventing release of a more mass-oriented media than other media. The author also attempts at highlighting themedium’s significance and integral connection with development communication and advancement of the masses at thegrassroots level of the society. The write up further includes an introduction to the medium’s emergence in the western world.